Respuesta :
Answer:
y = -10/3x -23
Step-by-step explanation:
The 2-point form of the equation of a line is useful for this.
y = (y2 -y1)/(x2 -x1)(x -x1) +y1
Using your points, we have ...
y = (-3 -7)/(-6 -(-9))(x -(-9)) +7
y = (-10/3)(x +9) +7
y = -10/3x -23 . . . . . . . simplify
![Ver imagen sqdancefan](https://us-static.z-dn.net/files/dc1/5bacc103e53711386efc294b5d0330fa.png)
Answer:
got it right on khan
Step-by-step explanation:
also give a heart and a 5 stars to the other guy, the only reason i posted was to prove his answer correct even further.
![Ver imagen yeetnoises8](https://us-static.z-dn.net/files/deb/ee7e32a35aedeb6a1500c5215f7f3b06.jpeg)